Performance Factors for Successful Business Incubators in Indonesian Public Universities - Lina Gozali; Maslin Masrom; Teuku Yuri M. Zagloel; Habibah N. Haron; Jose Arturo Garza-Reyes; Benny Tjahjono; Agustinus Purna Irawan; Frans Jusuf Daywin; Asril Fitri Syamas; Sani Susanto; Harry Kusuma Kiwi Aliwarga; Iveline Anne Marie (International Journal of Technology, 2020)
Measuring the performance of business processes is already a main concern for both faculty and enterprise players, since organizations are motivated to reach the productivity stage. Employing a performance achievement framework for the relationship between business incubator success factors will guarantee connection with commercial schemes, which support a high level of performance indicators in successful business incubator models. This research employs a quantitative approach, with the data analyzed using the IBM SPSS version 23 and Smart PLS version 3 statistical software packages. Employing a sample of 95 incubator managers from 19 universities which geographically located in Indonesia, it is shown that the image of business incubator factors has a positive effect on incubator performance. The study investigates the relationship between incubator performance and business incubator success factors in Indonesia. It was found that IT, as part of the business incubators’ facets/abilities, partially supports their performance; that the entry criteria directly support the performance of the incubators; that mentoring networks also support the performance, with good infrastructure systems as a moderating factor; that funding supports the performance of business incubators, also with good infrastructure systems as a moderating factor; and that university regulations and government support and protection enhance the performance  of  business incubators, with credits  and  rewards as a moderating factor.  In addition, a variety of indicators from the local context affiliate positively to promote a community that highlighted the incubators’ strategies.